Keseimbangan Dunia Dan Akhirat Dalam Kewirausahaan Islami: Eksplorasi Pada UMKM Berbasis Syariah - Faricha Noor Aida (Journal of Creative Power and Ambition (JCPA), 2025)
Islamic entrepreneurship plays an important role in the development of sharia-based MSMEs in Indonesia, which prioritizes a balance between worldly and hereafter goals. This study aims to explore how sharia MSMEs can apply Islamic economic principles in their business operations, such as transparency, fairness, and social responsibility, and face the challenges in creating this balance. The method used is a qualitative approach with case studies, in-depth interviews, direct observation, and analysis of related documents. The results of the study indicate that the application of sharia principles in sharia-based MSMEs not only pays attention to aspects of material profit, but also emphasizes social sustainability through zakat, infaq, and sadaqah. The main challenge faced is how to maintain a balance between financial profit and religious values, especially in facing competitive market competition. This study also highlights the importance of collaboration between MSMEs, sharia financial institutions, the government, and educational institutions in supporting the development of sharia-based MSMEs. Overall, this study provides insight into the development of sustainable Islamic entrepreneurship and provides positive social contributions to Indonesian society.